Cellulose particles and cosmetic containing cellulose particles

By forming a coating layer on the masterbatch of the cellulose particles and optimizing their structural parameters, the shortcomings of the cellulose particles in terms of hydrophobicity and dispersion are solved, and cosmetic properties with high sweat resistance and makeup resistance are achieved.

CN119908972APending Publication Date: 2025-05-02FUJIFILM BUSINESS INNOVATION CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411149483.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-31
Filing Date
2024-08-21
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing cellulose particles have shortcomings in hydrophobicity and dispersion, especially in terms of roundness and the ratio of carbon atomic weight to oxygen atomic weight, which fails to achieve excellent performance.

Method used

A specific Cs/Os ratio (such as ≥2.0 or ≥4.0) is met by forming a coating layer on the masterbatch of the cellulose particles and optimizing its structural parameters, such as the average roundness and the ratio of carbon atomic weight to oxygen atomic weight, to satisfy a specific Cs/Os ratio (such as ≥2.0 or ≥4.0) to improve hydrophobicity and dispersion.

Benefits of technology

The high hydrophobicity and dispersion of cellulose particles are achieved, thereby improving their sweat resistance and makeup resistance in cosmetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005003224690000151
    Figure BDA0005003224690000151
  • Figure BDA0005003224690000161
    Figure BDA0005003224690000161
  • Figure BDA0005003224690000171
    Figure BDA0005003224690000171
Patent Text Reader

Abstract

Disclosed are: cellulose particles having a master batch containing cellulose as a main component and a coating layer that coats the master batch, the average circularity of the cellulose particles being 0.97 or more; the relationship between the atomic weight of carbon Cs and the atomic weight of oxygen Os as measured by X-ray photoelectron spectroscopy satisfies formula A1: Cs / Os > = 2.0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to cellulose particles and cosmetics containing the cellulose particles. Background Art

[0002] Japanese Patent Gazette No. 6921293 proposes "a resin bead obtained by surface treating a core bead formed of a resin mainly composed of cellulose with a solid surface treatment agent, the cumulative 50% particle size based on volume being 50 μm or less, the sphericity being 0.7 to 1.0, the surface smoothness being 70 to 100%, and the crystallinity being 60% or less."

[0003] Japanese Patent Gazette No. 6694559 proposes "a particle containing cellulose acetate, wherein the average particle size of the particles is 80 nm to 100 μm, the sphericity is 0.7 to 1.0, the surface smoothness is 80% to 100%, and the surface contact angle with respect to water is 100° or more, and the total degree of acetyl substitution of the cellulose acetate is 0.7 to 2.9."

[0004] Japanese Patent Gazette No. 2022-22947 proposes "a biodegradable resin particle comprising: a masterbatch containing a biodegradable resin; a first layer present on the surface of the masterbatch and containing at least one cationic resin selected from polyalkylene imine, polyallylamine and polyethylene amine; and a second layer present on the first layer and containing an anionic or nonionic hydrophobic compound." Summary of the invention

[0005] The object of the present invention is to provide a cellulose particle having a master particle mainly composed of cellulose and a coating layer for coating the master particle, wherein the cellulose particle has excellent hydrophobicity and dispersibility compared with the following case: in the above-mentioned cellulose particle, the roundness is less than 0.97, and the relationship between the carbon atomic weight Cs and the oxygen atomic weight Os measured by X-ray photoelectron spectroscopy does not satisfy the formula A1: Cs / Os≥2.0.

[0006] According to a first embodiment of the present invention, there is provided a cellulose particle comprising: a mother particle having cellulose as a main component; and a coating layer coating the mother particle, wherein the average roundness of the cellulose particle is greater than 0.97, and the relationship between the carbon atomic weight Cs and the oxygen atomic weight Os measured by X-ray photoelectron spectroscopy satisfies the formula A1: Cs / Os≥2.0.

[0007] According to a second aspect of the present invention, in the cellulose particles involved in the first aspect, the relationship between the carbon atomic weight Cs and the oxygen atomic weight Os satisfies Formula A2: Cs / Os≥4.0.

[0008] According to a third aspect of the present invention, in the cellulose particles according to the first or second aspect, the coating layer contains at least one coating material selected from the group consisting of fatty acids, fatty acid metal salts, amino acids, and amino acid salts.

[0009] According to a fourth aspect of the present invention, in the cellulose particles according to any one of the first to third aspects, a coating amount of the coating layer relative to the mother particle is 2% by mass or more and 30% by mass or less.

[0010] According to a fifth aspect of the present invention, in the cellulose particles according to the fourth aspect, a coating amount of the coating layer relative to the mother particle is 4 mass % or more and 15 mass % or less.

[0011] According to a sixth aspect of the present invention, in the cellulose particles according to any one of the first to fifth aspects, an intermediate layer is provided between the mother particle and the covering layer.

[0012] According to a seventh aspect of the present invention, in the cellulose particles according to the sixth aspect, the intermediate layer contains at least one intermediate material selected from the group consisting of polyamine compounds, polyquaternary ammonium salts, polysaccharide compounds, and polyacrylic acid.

[0013] According to an eighth aspect of the present invention, there is provided a cosmetic comprising the cellulose particles according to any one of the first to seventh aspects.

[0014] (Effect)

[0015] According to the above-mentioned first scheme, a cellulose particle is provided, which has a mother particle with cellulose as the main component and a coating layer covering the mother particle, and has excellent hydrophobicity and dispersibility compared with the following situation: in the above-mentioned cellulose particles, the roundness is lower than 0.97, and the relationship between the carbon atomic weight Cs and the oxygen atomic weight Os measured by X-ray photoelectron spectroscopy does not satisfy the formula A1: Cs / Os≥2.0.

[0016] According to the second aspect, there is provided cellulose particles having excellent hydrophobicity and dispersibility compared to a case where the relationship between the carbon atomic weight Cs and the oxygen atomic weight Os does not satisfy the formula A2: Cs / Os≥4.0.

[0017] According to the third aspect, there is provided cellulose particles having excellent hydrophobicity and dispersibility compared to the case where the coating layer contains stearyl stearate.

[0018] According to the fourth aspect, there is provided cellulose particles having excellent hydrophobicity and dispersibility compared with a case where the coating amount of the coating layer relative to the mother particle is less than 2% by mass or exceeds 30% by mass.

[0019] According to the fifth aspect, there is provided cellulose particles having excellent hydrophobicity and dispersibility compared with a case where the coating amount of the coating layer relative to the mother particle is less than 4% by mass or exceeds 15% by mass.

[0020] According to the sixth aspect, there is provided a cellulose particle having excellent hydrophobicity and dispersibility compared to a case where no intermediate layer is provided between the mother particle and the coating layer.

[0021] According to the seventh aspect, there is provided a cellulose particle having excellent hydrophobicity and dispersibility compared to a case where the intermediate layer contains carbomer.

[0022] According to the above-mentioned eighth scheme, a cosmetic is provided, which uses cellulose particles having a masterbatch with cellulose as the main component and a coating layer covering the masterbatch, and has excellent sweat resistance and makeup removal resistance compared to the following situation: in the above-mentioned cellulose particles, the roundness is lower than 0.97, and the relationship between the carbon atomic weight Cs and the oxygen atomic weight Os measured by X-ray photoelectron spectroscopy does not satisfy the formula A1: Cs / Os≥2.0. DETAILED DESCRIPTION

[0023] Hereinafter, an embodiment of the present invention will be described. These descriptions and examples are for illustrating the embodiment and do not limit the scope of the present invention.

[0024] In the numerical range of recording in stages in this specification, the upper limit or lower limit recorded in a numerical range can also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range of recording in this specification, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment.

[0025] Each component may also contain a plurality of corresponding substances.

[0026] When referring to the amount of each component in a composition, if there are multiple substances corresponding to each component in the composition, unless otherwise specified, the amount of each component refers to the total amount of the multiple substances present in the composition.

[0027] <Cellulose particles>

[0028] The cellulose particles of the present embodiment include mother particles containing cellulose as a main component and a coating layer coating the mother particles.

[0029] The cellulose particles of the present embodiment have an average circularity of 0.97 or more, and the relationship between the carbon atomic weight Cs and the oxygen atomic weight Os measured by X-ray photoelectron spectroscopy satisfies the formula A1: Cs / Os≥2.0.

[0030] The cellulose particles of the present embodiment have excellent hydrophobicity and dispersibility due to the above-mentioned structure. The reason for this is presumably as follows.

[0031] By setting the ratio of the carbon atomic weight Cs to the oxygen atomic weight Os in the cellulose particles (Cs / Os) to 2.0, the number of carbon atoms present on the particle surface increases, and the hydrophobicity improves.

[0032] On the other hand, by setting the average circularity of the cellulose particles in the state where the coating layer is formed on the mother particles mainly composed of cellulose to 0.97 or more, the particles are close to a true sphere, and the rolling property is improved. Therefore, the dispersibility is also improved.

[0033] As described above, it is estimated that the cellulose particles of the present embodiment are excellent in hydrophobicity and dispersibility.

[0034] In particular, since the cellulose particles of the present embodiment have excellent hydrophobicity and dispersibility, when applied to cosmetics, cosmetics excellent in sweat resistance and makeup removal resistance can be obtained.

[0035] In addition, makeup removal refers to a phenomenon in which cosmetics attached to the skin partially aggregate over time and appear in the form of lines, for example.

[0036] (Relationship between carbon atomic weight Cs and oxygen atomic weight Os)

[0037] The relationship between the carbon atomic weight Cs and the oxygen atomic weight Os measured by X-ray photoelectron spectroscopy in the cellulose particles of the present embodiment satisfies the following formula A1. Preferably, the relationship satisfies the following formula A2, and more preferably, the relationship satisfies the following formula A3.

[0038] Formula A1: Cs / Os ≥ 2.0

[0039] Formula A2: Cs / Os ≥ 4.0

[0040] Formula A3: Cs / Os ≥ 5.0

[0041] However, the upper limit of the ratio Cs / Os is, for example, 20 or less.

[0042] When the relationship between the carbon atomic weight Cs and the oxygen atomic weight Os satisfies the formula A1, that is, when the ratio Cs / Os is 2.0 or more, the carbon atomic weight exposed on the surface of the cellulose particles increases, and the hydrophobicity improves.

[0043] Examples of a method for adjusting the ratio Cs / Os to fall within the above range include a method of forming a coating layer by performing surface treatment with a coating material containing carbon in a plurality of steps.

[0044] Furthermore, the relationship between the carbon atomic weight Cs and the silicon atomic weight Sis measured by X-ray photoelectron spectroscopy in the cellulose particles of the present embodiment preferably satisfies the following formula B. That is, the silicon atomic weight Sis may be 0 atom % or a small amount.

[0045] Formula B: 0≤Sis / Cs≤0.01

[0046] By increasing the hydrophobicity of the surface of the cellulose particles using carbon atoms instead of silicon atoms, there is an advantage that the surface free energy is further reduced, and the resistance to makeup removal due to sweat, sebum, etc. can be further improved.

[0047] - Measurement of atomic weights using X-ray photoelectron spectroscopy -

[0048] The method for measuring the atomic weight (atom %) of each substance by X-ray photoelectron spectroscopy (XPS) is as follows: In addition, the measurement was performed on cellulose particles.

[0049] The "PHI5000 Versa Probe II manufactured by ULVAC-PHI" was used as an XPS measuring device, monochromatized A1Kα rays were used as the X-ray source, and the acceleration voltage was set to 15 kV for measurement. Specifically, the analysis area was set to 100 μmφ, and the number of each atom (carbon atom, silicon atom, and oxygen atom) was obtained based on the spectrum of each atom (carbon atom, silicon atom, and oxygen atom) measured, and the atomic weight (carbon atomic weight, silicon atomic weight, and oxygen atomic weight) relative to the total atomic weight in the measurement area was calculated.

[0050] Then, the carbon atomic weight, silicon atomic weight, and oxygen atomic weight when the cellulose particle surface is measured are determined as the carbon atomic weight Cs, the silicon atomic weight Sis, and the oxygen atomic weight Os.

[0051] However, when the compound contained in the coating layer does not contain silicon atoms, the amount of silicon atoms is 0 atom %.

[0052] (Average roundness)

[0053] The average circularity of the cellulose particles of the present embodiment is 0.97 or more, and is preferably 0.98 or more, and more preferably 0.99 or more, from the viewpoint of improving hydrophobicity and dispersibility.

[0054] Furthermore, the average circularity of the cellulose particles may ideally be 1.

[0055] Examples of a method for adjusting the average circularity to fall within the above range include a method of performing surface treatment with a coating material in a plurality of steps to form a coating layer.

[0056] The circularity of cellulose particles is determined from (circle equivalent circumference) / (circumference) [(circumference of a circle having the same projected area as the particle image) / (circumference of the particle projected image)]. Specifically, it is a value measured by the following method.

[0057] First, the cellulose particles to be measured were collected by suction to form a flat flow, and the particle image was captured as a still image by instantaneous stroboscopic light emission, and the particle image was analyzed by a flow-type particle image analyzer (FPIA-3000 manufactured by SYSMEX Co., Ltd.) to obtain the circularity. The number of samples for obtaining the circularity was set to 3500, and the arithmetic average was calculated, and the obtained value was set as the average circularity.

[0058] (Masterbatch)

[0059] The masterbatch is a particle on which the coating layer is to be formed, and contains cellulose as a main component.

[0060] Here, containing cellulose as the main component means that the content of cellulose is 90% by mass or more (preferably 95% by mass or more, 98% by mass or more, or 100% by mass) based on the mother particle.

[0061] The number average molecular weight of cellulose is preferably 37,000 or more, more preferably 45,000 or more.

[0062] The upper limit of the number average molecular weight of cellulose is not particularly limited, and may be, for example, 100,000 or less.

[0063] The number average molecular weight of cellulose was measured by gel permeation chromatography (differential refractometer Optilab T-rEX / manufactured by Wyatt Technology, multi-angle light scattering detector DAWN HELEOS II / manufactured by Wyatt Technology, columns TSKgel α-M and α-3000, 1 each / manufactured by Tosoh Corporation) using dimethylacetamide (added with 0.1 M lithium chloride) as a solvent.

[0064] - Other ingredients -

[0065] Other ingredients may also be included in the masterbatch.

[0066] Other components include, for example, plasticizers, flame retardants, compatibilizers, release agents, lightfast agents, weatherproof agents, colorants, pigments, modifiers, drip-proof agents, antistatic agents, hydrolysis-proof agents, fillers, reinforcing agents (glass fiber, carbon fiber, talc, clay, mica, glass flakes, ground glass, glass beads, crystalline silica, alumina, silicon nitride, aluminum nitride, boron nitride, etc.), acid acceptors for preventing the release of acetic acid (oxides such as magnesium oxide and aluminum oxide; metal hydroxides such as magnesium hydroxide, calcium hydroxide, aluminum hydroxide, and hydrotalcite; calcium carbonate; talc, etc.), reactive scavengers (for example, epoxy compounds, acid anhydride compounds, carbodiimide, etc.), and the like.

[0067] The content of other components is preferably 0% by mass or more and 5% by mass or less relative to the total amount of the master batch. Here, "0% by mass" means that other components are not contained.

[0068] (Coating layer)

[0069] The coating layer preferably contains a coating material selected from a hydrophobic compound. Specifically, the coating layer preferably contains a coating material selected from a compound having a carboxyl group, and in particular, preferably contains at least one coating material selected from the group consisting of a fatty acid, a fatty acid metal salt, an amino acid and an amino acid metal salt, and more preferably contains at least one coating material selected from the group consisting of a fatty acid metal salt and an amino acid metal salt. The ratio Cs / Os of these coating materials (particularly metal salts) is the above range, which improves the hydrophobicity of the coating layer, and the roundness is also easily improved, and the dispersibility is also improved.

[0070] In addition, it is preferred that the coating layer does not contain a Si-containing compound as a coating material, or even if it contains a Si-containing compound, the amount thereof is 1 mass % or less relative to the coating layer.

[0071] -fatty acid-

[0072] Fatty acids refer to straight-chain or branched saturated or unsaturated fatty acids. Fatty acids may also be a mixture of saturated fatty acids and unsaturated fatty acids.

[0073] The fatty acid is preferably a fatty acid having 14 to 22 carbon atoms (preferably 14 to 20 carbon atoms). Specific examples of the straight-chain fatty acid having 14 to 22 carbon atoms include behenic acid, arachidic acid, palmitic acid, stearic acid, isostearic acid, and myristic acid.

[0074] -Metal salts of fatty acids-

[0075] The fatty acid metal salt refers to a linear or branched saturated or unsaturated fatty acid metal salt. The fatty acid metal salt may also be a mixture of a saturated fatty acid metal salt and an unsaturated fatty acid metal salt.

[0076] Examples of the fatty acid metal salt include metal salts of fatty acids having 14 to 22 carbon atoms (preferably 14 to 20 carbon atoms). Examples of the fatty acid metal salts having 14 to 22 carbon atoms include metal salts of stearic acid, behenic acid, palmitic acid, myristic acid, and the like.

[0077] Examples of the metal in the fatty acid metal salt include metals having a valence of two or more.

[0078] Examples of the metal in the fatty acid metal salt include magnesium, calcium, aluminum, barium and zinc.

[0079] -Amino Acids-

[0080] Examples of the amino acid include amino acids having 12 to 30 carbon atoms (preferably 18 to 24 carbon atoms).

[0081] Specific examples of the amino acid include lauroyl lysine, lauroyl arginine, myristyl leucine, and stearoyl glutamic acid.

[0082] -Amino acid metal salt-

[0083] Examples of the amino acid metal salt include metal salts of amino acids having 12 to 30 carbon atoms (preferably 18 to 24 carbon atoms).

[0084] Specific examples of amino acids include metal salts of lauroyl lysine, lauroyl arginine, myristyl leucine, stearoyl glutamic acid, and the like.

[0085] Examples of the metal in the amino acid metal salt include metals having a valence of two or more.

[0086] Examples of the metal in the amino acid metal salt include magnesium, calcium, aluminum, barium and zinc.

[0087] From the viewpoint of improving hydrophobicity and dispersibility, the coating amount of the coating layer relative to the mother particle is preferably 2 mass % to 30 mass %, more preferably 4 mass % to 15 mass %, and further preferably 10 mass % to 30 mass %.

[0088] Here, the content of the coating material with respect to the entire coating layer is preferably 90% by mass or more and 100% by mass or less, and more preferably 95% by mass or more and 100% by mass or less.

[0089] - Middle layer -

[0090] The cellulose particles of this embodiment preferably have an intermediate layer between the mother particle and the coating layer. When the intermediate layer is provided, carbon atoms are oriented on the surface of the coating layer, the ratio Cs / Os is more likely to be within the above range, and the hydrophobicity is improved.

[0091] The intermediate layer preferably contains at least one intermediate material selected from the group consisting of polyamine compounds, polyquaternary ammonium salts, polysaccharide compounds, and polyacrylic acid.

[0092] The polyamine compound is a general term for aliphatic hydrocarbons having two or more primary amino groups.

[0093] Examples of the polyamine compound include polyalkylene imine, polyallylamine, polyvinylamine, and polylysine.

[0094] From the viewpoint of improving biodegradability, the polyalkylene imine is preferably a polyalkylene imine containing a structural unit having an alkylene group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms, more preferably 1 to 2 carbon atoms), and polyethylene imine is more preferred.

[0095] Examples of the polyallylamine include homopolymers and copolymers such as allylamine, allylamine amide sulfate, diallylamine, and dimethylallylamine.

[0096] Examples of the polyvinylamine include those produced by hydrolyzing poly(N-vinyl formamide) with an alkali, and specific examples thereof include "PVAM-0595B" manufactured by Mitsubishi Chemical Corporation.

[0097] The polylysine may be a substance extracted from natural products, a substance produced by transforming microorganisms, or a substance synthesized chemically.

[0098] Examples of the polyquaternium salt include polyquaternium-6, polyquaternium-7, polyquaternium-10, polyquaternium-11, polyquaternium-51, polyquaternium-61, and polyquaternium-64.

[0099] The content of the polyquaternium salt is preferably 0.2% by mass or more and 2% by mass or less based on the entire cellulose particles.

[0100] As polysaccharide compounds, chitin, chitosan, carboxymethyl cellulose, etc. can be enumerated. In addition, as polysaccharide compounds, polysaccharides with sulfuric acid or phosphoric acid, polysaccharides with uronic acid (e.g., glucuronic acid, iduronic acid, galacturonic acid, mannuronic acid), or polysaccharides with the structure of both of these acids, etc. can also be enumerated. Specifically, as polysaccharides, hyaluronic acid, gellan gum, deacylated gellan gum (DAG), neutral gum, diutan gum, xanthan gum, carrageenan, xanthan gum, hexuronic acid, fucoidan, pectin, pectic acid, pectinic acid, heparan sulfate, heparan sulfate, keratin sulfate, chondroitin sulfate, dermatan sulfate, rhamnosyl sulfate, alginic acid can be enumerated.

[0101] From the viewpoint of improving hydrophobicity and dispersibility, the coating amount of the intermediate layer relative to the mother particle is preferably 0.1% by mass or more and 20% by mass or less, and more preferably 0.2% by mass or more and 2% by mass or less.

[0102] Here, the content of the intermediate material with respect to the entire intermediate layer is preferably 90% by mass or more and 100% by mass or less, and more preferably 95% by mass or more and 100% by mass or less.

[0103] From the viewpoint of improving hydrophobicity and dispersibility, the ratio of the coating amount of the coating layer to the coating amount of the intermediate layer (i.e., ratio = coating amount of the coating layer / coating amount of the intermediate layer) is preferably greater than 0.05 and less than 400, more preferably greater than 1.5 and less than 150, and further preferably greater than 5 and less than 150.

[0104] -External additives-

[0105] The cellulose particles of this embodiment may also be added with inorganic particles. When inorganic particles are added, secondary aggregation of the particles is suppressed, so that the original properties of the particles are easily exerted. Therefore, the hydrophobicity and dispersibility are easily improved.

[0106] As the external additive, at least one selected from the group consisting of silicon-containing compound particles and metal oxide particles can be cited.

[0107] The silicon-containing compound particles refer to particles containing silicon.

[0108] The silicon-containing compound particles may be particles containing only silicon or particles containing silicon and other elements.

[0109] As the silicon-containing compound particles, silicon dioxide particles are preferred. As long as the silicon dioxide particles are composed of silicon dioxide, i.e., SiO 2 The silica particles may be particles containing the main component, and may be crystalline or amorphous. In addition, the silica particles may be particles produced using silicon compounds such as water glass and alkoxysilane as raw materials, or may be particles obtained by pulverizing quartz.

[0110] As the metal oxide, oxides of metals other than silicon can be used.

[0111] Examples of the metal oxide include zinc oxide, magnesium oxide, iron oxide, and aluminum oxide.

[0112] From the viewpoint of texture (specifically, skin feel), the volume average particle size of the external additive is preferably 1 nm or more and 100 nm or less, and more preferably 5 nm or more and 30 nm or less.

[0113] The volume average particle size of the external additive is measured by the same method as the volume average particle size of cellulose.

[0114] The amount of the external additive added is preferably 0.1% by mass or more and 2% by mass or less based on the total mass of the cellulose particles (cellulose particles to which no external additive is added).

[0115] (Volume average particle size)

[0116] The volume average particle size of the cellulose particles of the present embodiment is preferably 1 μm or more and 100 μm or less, more preferably 2 μm or more and 20 μm or less, and further preferably 4 μm or more and 10 μm or less.

[0117] By setting the volume average particle size of the cellulose particles of the present embodiment to 1 μm or more and 100 μm or less, the particle size becomes an appropriate size, and the hydrophobicity and dispersibility are improved.

[0118] The volume average particle size of the cellulose particles is measured as follows.

[0119] The particle size was measured using an LS particle size distribution analyzer "Beckman Coulter LS13 320 (Beckman Coulter)", and the cumulative distribution of the particle size was plotted from the smaller diameter side on a volume basis, and the particle size at which the cumulative distribution was 50% was determined as the volume average particle size.

[0120] <Method for producing cellulose particles>

[0121] The method for producing cellulose particles of the present embodiment includes, for example: a step of obtaining a master particle containing cellulose as the main component (hereinafter referred to as the "cellulose particle (master particle) production step"); and a step of coating the master particle with a coating material and an intermediate material as required (hereinafter referred to as the "intermediate layer and coating layer formation step").

[0122] Specifically, the method for producing cellulose particles according to the present embodiment is as follows, for example.

[0123] -Masterbatch manufacturing process-

[0124] (1) First, cellulose acylate is dissolved in a water-soluble organic solvent A to prepare a cellulose acylate solution A.

[0125] (2) Next, cellulose acylate solution A is added to a calcium carbonate dispersion prepared by dispersing calcium carbonate in water, and the mixture is stirred to prepare cellulose acylate solution B.

[0126] (3) Next, cellulose acylate solution B is added to a mixed solution of carboxymethyl cellulose, a water-soluble organic solvent B and water, and the mixture is stirred at high speed to prepare cellulose acylate solution C.

[0127] (4) Next, after sodium hydroxide is added to the cellulose acylate solution C, the cellulose acylate dispersion C is heated to remove the water-soluble organic solvents A and B, and hydrochloric acid is added to form cellulose acylate particles. The cellulose acylate particles are then filtered and the filtered cellulose acylate particles are dispersed in water to prepare a cellulose acylate particle dispersion.

[0128] (5) Next, after sodium hydroxide is added to the cellulose acylate particle dispersion, the cellulose acylate particle dispersion is heated and stirred in a weak alkaline environment to saponify the cellulose acylate particles, thereby preparing a mother particle suspension.

[0129] (6) Next, hydrochloric acid is added to the mother particle suspension to adjust the pH of the suspension to near neutral (e.g., in the range of 6.5 to 7), and then the mother particles are filtered out and washed with pure water repeatedly. After the conductivity of the filtrate reaches 10 μs / cm or less, the filtered mother particles are dried.

[0130] Here, cellulose acylate refers to a cellulose derivative in which at least one of the hydroxyl groups in cellulose is substituted (acylated) with an aliphatic acyl group. Specifically, at least one of the hydroxyl groups in cellulose is substituted with a -CO-R AC (R AC represents an aliphatic hydrocarbon group. ) substituted cellulose derivative.

[0131] The water-soluble organic solvent A is a solvent in which water is dissolved in an amount of 0.1% by mass to 10% by mass relative to the solvent at 25° C., and examples thereof include ethyl acetate and butyl acetate.

[0132] The water-soluble organic solvent B is a solvent in which water is dissolved in an amount of 0.1% by mass to 10% by mass relative to the solvent at 25° C., and examples thereof include methyl ethyl ketone and acetone.

[0133] - Intermediate layer and coating layer forming process -

[0134] First, an aqueous dispersion in which the master particles are dispersed is prepared. Before preparing the aqueous dispersion, the master particles are preferably washed with an acid.

[0135] Next, the aqueous dispersion containing the masterbatch is mixed with the aqueous solution containing the intermediate material constituting the intermediate layer. Thus, for example, the hydroxyl group of the cellulose contained in the masterbatch reacts with the amine position, carboxyl group, amino group, etc. of the compound constituting the intermediate layer, or the hydroxyl group undergoes hydrogen bonding, thereby forming the intermediate layer. In addition, the operation of forming the intermediate layer can be performed multiple times.

[0136] However, when the intermediate layer is not formed, this operation is not performed.

[0137] Then, after heating the aqueous dispersion in which the master particles forming the intermediate layer are dispersed, the coating material constituting the coating layer is added and stirred. Thus, the coating layer is formed. In addition, it is preferred that the operation of forming the coating layer is performed multiple times.

[0138] Here, when forming the coating layer, the coating amount of the coating layer is controlled by the heating temperature, the amount of coating material added, the time of adding the coating material, and the stirring time after adding the coating material.

[0139] Then, the masterbatch with the coating layer is taken out from the mixed solution. The removal of the masterbatch with the coating layer is implemented, for example, by filtering the mixed solution. The taken out masterbatch with the coating layer is preferably washed with water. In this way, the unreacted intermediate material and the coating material can be removed. Then, the masterbatch with the coating layer is dried to obtain the cellulose particles of this embodiment.

[0140] - External Additive Process -

[0141] An external additive may be added to the obtained cellulose particles.

[0142] The external addition step includes, for example, a treatment of adding an external additive to cellulose particles using a mixing mill, a V-type mixer, a Henschel mixer, a Lödige mixer, or the like.

[0143] <Application>

[0144] Examples of uses of the cellulose particles of this embodiment include cosmetics, rolling agents, abrasives, scrubbing agents, display spacers, bead molding materials, light scattering particles, resin reinforcing agents, refractive index control agents, biodegradation accelerators, fertilizers, water-absorbing particles, toner particles, and granular bodies of anti-caking particles.

[0145] <Cosmetics>

[0146] The cosmetic according to the present embodiment is a cosmetic containing the cellulose particles according to the present embodiment.

[0147] The cosmetics of this embodiment include, for example, base makeup cosmetics (e.g., primer, concealer, foundation cream, face powder, etc.); beauty cosmetics (e.g., lipstick, lip gloss, lip liner, blush, eye shadow, eyeliner, mascara, eyebrow pencil, nail polish, nail care cosmetics, etc.); skin care cosmetics (e.g., facial cleanser, makeup remover, lotion, emulsion, beauty serum, pack, facial mask, eye and mouth care cosmetics, etc.), etc.

[0148] In particular, the cosmetic of the present embodiment is preferably a beauty cosmetic because of its high perspiration resistance and makeup removal resistance.

[0149] [Example]

[0150] Hereinafter, examples will be described, but the present invention is not limited to these examples. In the following description, "parts" and "%" are all based on mass unless otherwise specified.

[0151] <Preparation of various materials>

[0152] Prepare the following materials.

[0153] <Examples 1 to 17, Comparative Examples 1 to 3>

[0154] - Formation of Masterbatch -

[0155] 130 parts of DAC "L-50 manufactured by Daicel Corporation, cellulose diacetate, weight average degree of polymerization 570" as cellulose acylate are completely dissolved in 870 parts of ethyl acetate. Add it to a dispersion prepared by dispersing 50 parts of calcium carbonate in 500 parts of pure water, and stir for 3 hours. Add it to a dispersion prepared by dispersing 4 parts of carboxymethyl cellulose and 200 parts of methyl ethyl ketone in 600 parts of pure water, and stir for 5 minutes with a high-speed emulsifier. Add 10 parts of sodium hydroxide to it, stir at 80°C for 3 hours, and remove ethyl acetate and methyl ethyl ketone. Add 10 parts of dilute hydrochloric acid to it to dissolve calcium carbonate. Filter the residue and disperse it again in pure water to obtain a slurry of cellulose acylate particles.

[0156] 17.5 parts of a 20% aqueous sodium hydroxide solution were added to 500 parts of a slurry of cellulose acylate particles (solid content 10%), and the mixture was stirred at 30°C for 6 hours to saponify the cellulose acylate particles. Hydrochloric acid was added dropwise until the pH of the slurry reached 7. After that, the slurry was filtered, and the filtrate was washed with an excess of pure water. The filtration and washing were repeated until the conductivity of the filtrate reached 10 μs / cm or less. Finally, the cake-like filtrate obtained was filtered, and the filtrate was freeze-dried to obtain saponified cellulose master particles.

[0157] - Surface treatment -

[0158] The cake-like cellulose mother particles that were repeatedly filtered and washed until the conductivity of the filtrate became 10 μs / cm or less were re-slurried with pure water to obtain a mother particle slurry.

[0159] The intermediate materials of the types and amounts shown in Table 1 were added to 500 parts of the masterbatch slurry (solid content 10%), and the stirring was continued for the stirring time shown in Table 1 while maintaining the temperature at 35°C. The treatment was performed for the number of times shown in Table 1 (the table indicates the number of treatments). Thus, an intermediate layer with the coating amount shown in Table 1 was formed on the masterbatch.

[0160] Next, after the master particle slurry with the intermediate layer formed therein is heated to 80°C, the master particle slurry is added with the type and amount of coating material shown in Table 1, and then stirred for the stirring time shown in Table 1. The treatment is performed the number of times shown in Table 1 (the table indicates the number of treatments). Thus, a coating layer with the coating amount shown in Table 1 is formed on the intermediate layer.

[0161] Thereafter, the mother particles with the intermediate layer and the coating layer formed thereon were repeatedly filtered and washed until the conductivity of the filtrate was 10 μs / cm or less. After washing, the obtained cake was dried to obtain cellulose particles having the intermediate layer and the coating layer.

[0162] The obtained pellets were mixed in an FM mixer (FM40, manufactured by Nippon Coke Industry Co., Ltd.) at a temperature of 25° C. for 4000 min. -1 The mixture was stirred at a speed of 2 h to make the surface of the coating layer smooth.

[0163] In addition, as indicated by "-" in Table 1, in some examples, cellulose particles were produced without forming an intermediate layer, or without forming an intermediate layer and a covering layer.

[0164] <Comparative Examples 4 and 5>

[0165] The following commercially available cellulose particles were respectively used as cellulose particles of Comparative Examples 4 and 5.

[0166] Comparative Example 4: Daito Chemical Industry Co., Ltd. "S-STM CELLULOBEADSD-5"

[0167] Comparative Example 5: Daito Chemical Industry Co., Ltd. "OTS-0.5A CELLULOBEADSD-10"

[0168] <Evaluation>

[0169] (Particle properties)

[0170] The cellulose particles obtained in each example were measured for the following particle properties according to the above-mentioned methods.

[0171] ・The ratio of carbon atomic weight Cs to oxygen atomic weight Os (Cs / Os) measured by X-ray photoelectron spectroscopy

[0172] Average roundness

[0173] Volume average particle size of cellulose particles

[0174] (Artificial sweat contact angle)

[0175] Using the cellulose particles of each example and according to the formulation shown in Table 2, a liquid foundation was obtained by a known method.

[0176] The foundation liquid was applied on the artificial skin and left to stand at room temperature for 1 hour. Artificial sweat was dropped using a contact angle meter to measure the artificial sweat contact angle. The evaluation criteria were as follows.

[0177] A: 100°≤contact angle

[0178] B: 90°≤Contact angle≤100°

[0179] C: Contact angle <90°

[0180] (Makeup removal)

[0181] Using the cellulose particles of each example and according to the formulation shown in Table 2, a liquid foundation was obtained by a known method.

[0182] Ten subjects were asked to place 5 g of liquid foundation on the back of their hands and apply it. After 8 hours, the subjects rated the makeup removal on a 10-point scale, with the best being 10 and the worst being 0. The scores of the ten subjects were arithmetic averaged for evaluation.

[0183] [Table 1-1]

[0184]

[0185] [Table 1-2]

[0186]

[0187] [Table 2]

[0188]

[0189] The above results show that the cellulose particles of this example are superior in sweat resistance and makeup removal resistance compared to the cellulose particles of the comparative example.

[0190] This also shows that the cellulose particles of this example are superior in hydrophobicity and dispersibility compared to the cellulose particles of the comparative example.

[0191] (Note) (((1)))

[0193] A cellulose particle having:

[0194] A masterbatch having cellulose as a main component; and

[0195] a coating layer that covers the masterbatch,

[0196] The average roundness of the cellulose particles is greater than 0.97,

[0197] The relationship between the carbon atomic weight Cs and the oxygen atomic weight Os measured by X-ray photoelectron spectroscopy satisfies the formula A1: Cs / Os≥2.0. (((2)))

[0199] The cellulose particles according to (((1))), wherein

[0200] The relationship between the carbon atomic weight Cs and the oxygen atomic weight Os satisfies Formula A2: Cs / Os≥4.0. (((3)))

[0202] The cellulose particles according to (((1))) or (((2))), wherein

[0203] The coating layer contains at least one coating material selected from the group consisting of fatty acids, fatty acid metal salts, amino acids, and amino acid salts. (((4)))

[0205] The cellulose particles according to any one of (((1))) to (((3))), wherein

[0206] The coating amount of the coating layer relative to the mother particle is 2 mass % or more and 30 mass % or less. (((5)))

[0208] The cellulose particles according to (((4))), wherein

[0209] The coating amount of the coating layer relative to the mother particle is 4 mass % or more and 15 mass % or less. (((6)))

[0211] The cellulose particles according to any one of (((1))) to (((5))), wherein

[0212] An intermediate layer is provided between the master particle and the coating layer. (((7)))

[0214] The cellulose particles according to (((6))), wherein

[0215] The intermediate layer contains at least one intermediate material selected from the group consisting of polyamine compounds, polyquaternary ammonium salts, polysaccharide compounds and polyacrylic acid. (((8)))

[0217] A cosmetic comprising the cellulose particles according to any one of (((1))) to (((7))).

[0218] According to (((1))), a cellulose particle is provided, which has a mother particle with cellulose as the main component and a coating layer covering the mother particle, and has excellent hydrophobicity and dispersibility compared with the following situation: in the above-mentioned cellulose particles, the roundness is less than 0.97, and the relationship between the carbon atomic weight Cs and the oxygen atomic weight Os measured by X-ray photoelectron spectroscopy does not satisfy the formula A1: Cs / Os≥2.0.

[0219] According to (((2))), there is provided a cellulose particle having excellent hydrophobicity and dispersibility compared with a case where the relationship between the carbon atomic weight Cs and the oxygen atomic weight Os does not satisfy the formula A2: Cs / Os ≥ 4.0.

[0220] According to (((3))), there is provided cellulose particles having excellent hydrophobicity and dispersibility compared with a case where the coating layer contains stearyl stearate.

[0221] According to (((4))), there is provided a cellulose particle having excellent hydrophobicity and dispersibility compared with a case where the coating amount of the coating layer with respect to the mother particle is less than 2 mass % or exceeds 30 mass %.

[0222] According to (((5))), there is provided cellulose particles having excellent hydrophobicity and dispersibility compared with a case where the coating amount of the coating layer with respect to the mother particle is less than 4 mass % or exceeds 15 mass %.

[0223] According to (((6))), there is provided a cellulose particle having excellent hydrophobicity and dispersibility compared with a cellulose particle having no intermediate layer between a mother particle and a coating layer.

[0224] According to (((7))), there is provided a cellulose particle having excellent hydrophobicity and dispersibility compared with a cellulose particle in which the intermediate layer contains carbomer.

[0225] According to (((8))), a cosmetic is provided, which uses cellulose particles having a masterbatch with cellulose as the main component and a coating layer covering the masterbatch, and has excellent sweat resistance and makeup removal resistance compared to the following situation: in the above-mentioned cellulose particles, the roundness is less than 0.97, and the relationship between the carbon atomic weight Cs and the oxygen atomic weight Os measured by X-ray photoelectron spectroscopy does not satisfy the formula A1: Cs / Os≥2.0.

Claims

1. A cellulose particle, characterized in that: have: A masterbatch having cellulose as a main component; and a coating layer that covers the masterbatch, The average roundness of the cellulose particles is greater than 0.97, The relationship between the carbon atomic weight Cs and the oxygen atomic weight Os measured by X-ray photoelectron spectroscopy satisfies the formula A1: Cs / Os≥2.

0.

2. The cellulose particles according to claim 1, wherein The relationship between the carbon atomic weight Cs and the oxygen atomic weight Os satisfies Formula A2: Cs / Os≥4.

0.

3. The cellulose particles according to claim 1 or 2, wherein The coating layer contains at least one coating material selected from the group consisting of fatty acids, fatty acid metal salts, amino acids, and amino acid salts.

4. The cellulose particles according to any one of claims 1 to 3, wherein The coating amount of the coating layer relative to the mother particle is 2 mass % or more and 30 mass % or less.

5. The cellulose particles according to claim 4, wherein The coating amount of the coating layer relative to the mother particle is 4 mass % or more and 15 mass % or less.

6. The cellulose particles according to any one of claims 1 to 5, wherein An intermediate layer is provided between the master particle and the coating layer.

7. The cellulose particles according to claim 6, wherein The intermediate layer contains at least one intermediate material selected from the group consisting of polyamine compounds, polyquaternary ammonium salts, polysaccharide compounds and polyacrylic acid.

8. A cosmetic, characterized in that: Containing the cellulose particles according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Biodegradable resin particle

    JP2022022947A